Strategi Peningkatan Daya Saing UMKM Dalam Menghadapi Masyarakat Ekonomi ASEAN - Andarini, Sonja; Ikaningtyas, Maharani; Putri, Ratna Kusumawati; Fitria, Anggita Dini; Kartika, Ragita Widya (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In order to achieve stable and sustainable economic growth, it is necessary to support solid macroeconomic and financial system stability. Micro, Small, and Medium Enterprises (MSMEs) in Indonesia are getting serious attention to the government and the community's disability. Indonesia is progressing from year to year which cannot be underestimated. However, Indonesia must be more persistent in improving quality in all sectors of the economy, increasing competitiveness by utilizing advances in information and communication technology that are increasingly advanced as they are today. Why do Indonesian MSMEs have the right to improve the welfare of the Indonesian people and national economic growth, especially in the face of the ASEAN free market? And how are possible strategy efforts to be implemented for the government and Indonesian MSME business people? This study aims to provide an explanation of the form of efforts to Increase the Competitiveness of MSMEs in Facing the ASEAN Economic Community. This study uses a descriptive analytical research method to provide a complete picture of the current power of MSMEs. The approach used in this study is a qualitative approach through critical appraisal. The ability of MSMEs to face the flow of global competition does need to be further thought about in order to survive for the stability of the Indonesian economy.